The impact of inclusive architectural strategies on social inclusion characteristics in innovation hubs in Southwest Nigeria - Ekhaese, Eghosa Noel; Oyelude, Felicia (Frontiers in Built Environment, 2025)
Innovation hubs foster collaboration, creativity, and economic growth. However, the inclusivity of these spaces remains a critical factor in ensuring equal access and participation by diverse users. This study examined the impact of inclusive architectural design strategies on social inclusion in selected innovation hubs in Nigeria. This study focuses on how these strategies create accessible, collaborative, and equitable spaces. This research identifies the inclusive architectural strategies applicable in innovation hubs and examines the impact of inclusive architectural strategies on improving social inclusion characteristics in innovation hubs. The study used a quantitative method based on structured questionnaires, which reached 170 participants distributed across five innovation hubs in Southwest, Nigeria. The researchers used descriptive and inferential statistical analysis combined with frequency counts and percentages for data evaluation that produced graphical representations. Findings reveal that inclusive architectural elements, such as accessibility compliance, spatial flexibility, and user-centred design, significantly influence social interactions, knowledge exchange, and engagement within innovation hubs. However, barriers such as inadequate planning, lack of policy enforcement, and financial constraints hinder the full implementation of inclusive design principles. The study concludes that integrating inclusive architectural strategies from the initial planning stages can enhance accessibility and foster greater social participation in innovation hubs. By prioritising universal design principles, these spaces can bridge socio-economic gaps, promote innovation, and support diverse user needs. The findings provide valuable insights for architects, policymakers, and stakeholders in developing more inclusive and sustainable innovation environments.